2019
DOI: 10.1039/c9nj03986d
|View full text |Cite
|
Sign up to set email alerts
|

Two zinc(ii)-based coordination polymers with flexible dicarboxylate and pyridine mixed ligands: effect of π⋯π interactions on electrical activity

Abstract: We synthesized two Zn(ii)-based 1D coordination polymers with paddle-wheel units using flexible 1,4-cyclohexanedicarboxylate linkers; these compounds exhibited electrical conductivity and Schottky barrier diode behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Panda and Banerjee established the role of π···π interactions in conducting property of 2D layered In­(III)-isophthalate CP . Akhtaruzzaman et al have shown that with increase in interchain π···π interactions, the conductivity increases by using two different 1D CPs ([Zn­( cis -1,4-chdc)­(4-phpy)]­n and [Zn­( cis -1,4-chdc)­(py)]­n, (1,4-H2chdc = 1,4-cyclohexanedicarboxylicacid, 4-phpy = 4 phenyl pyridine, and py = pyridine) . The former compound shows superior conductivity than later one, and the authors demonstrated that this 1D coordination chains are assembled through π···π interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Panda and Banerjee established the role of π···π interactions in conducting property of 2D layered In­(III)-isophthalate CP . Akhtaruzzaman et al have shown that with increase in interchain π···π interactions, the conductivity increases by using two different 1D CPs ([Zn­( cis -1,4-chdc)­(4-phpy)]­n and [Zn­( cis -1,4-chdc)­(py)]­n, (1,4-H2chdc = 1,4-cyclohexanedicarboxylicacid, 4-phpy = 4 phenyl pyridine, and py = pyridine) . The former compound shows superior conductivity than later one, and the authors demonstrated that this 1D coordination chains are assembled through π···π interactions.…”
Section: Resultsmentioning
confidence: 99%
“…5. For the monodentate terminal ligands, pyridine derivatives are the most popular ligands for constructing 0D 58 and 1D 59 CPs with 1,2- or 1,4-CHDC, which can be considered as two-connected linkers. Interestingly, Lin et al showed that the 1e,4a-CHDC ligands bridge the Cd 2+ cations to form trinuclear cluster-based chains which are further linked by 1e,4e-CHDC ligands into a 2D network (Fig.…”
Section: Auxiliary Ligands In Coordination Structuresmentioning
confidence: 99%
“…In the advancement of modern science, supramolecular chemistry plays a crucial role as it contributes actively in the area of synthetic materials. Over the years, hydrogen bonding and π···π stacking interactions have remained the most familiar supramolecular forces and play crucial roles in many chemical and biological processes. The existence of halogen-related interactions in organic crystal engineering is also well-established. However, their associations within metal coordination networks are relatively less explored. , …”
Section: Introductionmentioning
confidence: 99%